HIV, STD, and Sexual Risk Reduction for Individuals with a Severe Mental Illness: Review of the Intervention Literature - Senn, Theresa E.; Carey, Michael P. (Current Psychiatry Reviews, 2008)
Seroprevalence studies indicate that HIV infection rates are elevated among individuals with a severe mental illness (SMI) compared to the general population. The higher prevalence of HIV among individuals with SMI has prompted the development and evaluation of tailored sexual risk reduction programs for these individuals. In this paper, we review the literature on sexual risk-reduction interventions for individuals with SMI, including interventions for both uninfected and infected individuals. We discuss components of successful interventions, identify limitations in the current literature, and highlight directions for future research. Finally, we conclude with implications for clinical practice, including a discussion of the challenges and advantages to implementing sexual risk reduction interventions for individuals with SMI.
Keywords: severe mental illness